Interaction analysis of youth participation with the household waste management system regarding the existence of local waste treatment facilities - Naldi, Ari (Interaction, Community Engagement, and Social Environment, 2023)
Community participation is inseparable from youth participation to achieve sustainable household waste management. Some research pointed out that the presence of a waste treatment facility (WTF) near the waste generator may influence community participation in waste management but only a few of them discussed the relationship between WTF and youth participation. This paper discusses about WTF’s impact on youth participation in household waste management with a case study in Paulan Village, Central Java. Paulan Village has succeeded to stop transporting waste to the regional landfill since the local government operates WTF in mid-2019. However, does its existence influence youth participation in household waste management? This study used field observation, questionnaires, and in-depth interview methods, involving four key informants. Based on the descriptive content analysis, it was found that the presence of local WTF does not have a strong influence on increasing youth participation unless there is intensive intervention involving stakeholders, especially the local government. This paper suggests that intensive campaigns, like monthly or bimonthly socialization, and rewards are needed to optimize youth participation in household waste management. Besides, adults’ intervention is also needed in guiding the young generation to give more contributions to the community by involving in household waste management.